Co-cultivo de bactérias ácido láticas e Saccharomyces cerevisiae para melhoria do processo fermentativo de produção de cachaça - Flávia Barbosa Magalhães Alvarenga (2023)
Cachaça, a distilled spirit obtained through the fermentation of sugarcane juice, plays a significant role both in the cultural context and in the economic sphere of the country. The present study aimed to investigate the application of lactic acid bacteria (LAB) strains in co-fermentation with Saccharomyces cerevisiae for cachaça production, as well as the use of these bacteria in a wine re-fermentation step. A process similar to this re-fermentation step is used in wine and whisky production, where bacterial fermentation is employed to impart a greater diversity of aromas and flavors. A total of twenty-six isolates of LAB, derived from cachaça fermentation vats, were selected for fermentation tests. These isolates were identified through sequencing of the small subunit of the rRNA gene. The LAB were subjected to growth assays in a synthetic medium similar to sugarcane juice and bench-scale fermentations. Sugar consumption, as well as ethanol and glycerol synthesis, were analyzed, along with yield, efficiency, and productivity parameters. Subsequently, the production of cachaça was carried out on a pilot scale, encompassing both the fermentation and distillation stages. Additionally, analyses of secondary compounds generated during the process were performed, along with the concentration of copper present in the samples. From the conducted tests, two lactic acid bacteria were selected: Lacticaseibacillus paracasei CO30547 and Lactiplantibacillus plantarum BALS1.1. These exhibited highly satisfactory performance in all experiments conducted. Cachaças obtained through re-fermentation showed higher amounts of ethyl acetate, an important aromatic compound related to the beverage's flavor, compared to those produced through co-fermentation. The obtained results revealed that the chosen bacteria had a positive influence on the cachaça fermentation process, promoting the generation of desirable volatile compounds and remaining in compliance with predetermined legal limits.